2008
DOI: 10.1103/physreve.78.036702
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic consistency of liquid-gas lattice Boltzmann methods: Interfacial property issues

Abstract: In the present study we examine the thermodynamic consistency of lattice Boltzmann equation (LBE) models that are based on the forcing method by comparing different numerical treatments of the LBE for van der Waals fluids. The different models are applied for the calculation of bulk and interfacial thermodynamic properties at various temperatures. The effect of the interface density gradient parameter, kappa , that controls surface tension, is related explicitly with the fluid characteristics, including temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…It can be seen that both of them are in good agreement with the solution given by the Maxwell construction. Here it should also be pointed out that, for circular interfaces, the coexistence liquid and vapor densities will vary with the droplet size according to Laplace's law [45]. To reduce the influence of droplet size, an alternative choice may be a piecewise equation of state, which can offer a separate control of ∂p/∂ρ in every single phase region and the mixed region [46].…”
Section: B Interface Thickness and Spurious Velocitymentioning
confidence: 99%
“…It can be seen that both of them are in good agreement with the solution given by the Maxwell construction. Here it should also be pointed out that, for circular interfaces, the coexistence liquid and vapor densities will vary with the droplet size according to Laplace's law [45]. To reduce the influence of droplet size, an alternative choice may be a piecewise equation of state, which can offer a separate control of ∂p/∂ρ in every single phase region and the mixed region [46].…”
Section: B Interface Thickness and Spurious Velocitymentioning
confidence: 99%
“…However, there are variations of the pressure across the interface, which indicates that the mechanical stability condition is not satisfied around the interface. This issue happens in the lattice Boltzmann methods by using a force to introduce the nonideal EOS (for more details see [59][60][61][62]). The temperature distributions at different times are also shown in Fig.…”
Section: B Stationary Evaporating Dropletmentioning
confidence: 99%
“…In the past two decades, many researchers showed that lattice Boltzmann method is very suitable for simulation of two-phase systems [11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%